EUROPEAN SOLUTION OF ROAD TRANSPORT SAFETY - Sukalova, Viera; Ceniga, Pavel (Doprava a spoje, 2012)
Road transport safety is a serious social problem in Slovak Republic, but also in European Union. Increasing of road safety can be realized only by common measures and their using in everyday life. It is not only the harmonization and development of new technologies and intelligent transport systems, but also to develop a comprehensive strategic action in the accident, the emergency services, the definitions of the classification of injuries and deaths as a preparation for the adoption of a target to reduce the number of injuries, focus on training and training users, encourage the use of safety equipment and pay particular attention to the most vulnerable users such as pedestrians, cyclists and motorcyclists, including through safer infrastructure and vehicle technology.